(untitled) - Pratt, David (Australia, 2004)
Now in its second edition, this essential book clearly and precisely explains all the procedures involved in compiling an estimate of the cost of construction work. Modern, updated coverage includes quantity takeoff, pricing of the contractor’s work, pricing subtrade work, pricing site overheads, and compiling bid documents. This thorough grounding in the principles of construction estimating offers readers the skills required to successfully perform the work of a professional estimator. Drawings for two complete projects – one residential and one commercial – lead users through the complete estimating process for each and forms a basic framework that can easily be applied to various trades on many different types of construction projects.
Keywords: Building; Estimates